The Rattlesnake W Chromosome: A GC-Rich Retroelement Refugium with Retained Gene Function Across Ancient Evolutionary Strata. (22nd July 2022) - Schield, Drew R; Perry, Blair W; Card, Daren C; Pasquesi, Giulia I M; Westfall, Aundrea K; Mackessy, Stephen P; Castoe, Todd A
Abstract: Sex chromosomes diverge after the establishment of recombination suppression, resulting in differential sex-linkage of genes involved in genetic sex determination and dimorphic traits. This process produces systems of male or female heterogamety wherein the Y and W chromosomes are only present in one sex and are often highly degenerated. Sex-limited Y and W chromosomes contain valuable information about the evolutionary transition from autosomes to sex chromosomes, yet detailed characterizations of the structure, composition, and gene content of sex-limited chromosomes are lacking for many species. In this study, we characterize the female-specific W chromosome of the prairie rattlesnake ( Crotalus viridis ) and evaluate how recombination suppression and other processes have shaped sex chromosome evolution in ZW snakes. Our analyses indicate that the rattlesnake W chromosome is over 80% repetitive and that an abundance of GC-rich mdg4 elements has driven an overall high degree of GC-richness despite a lack of recombination. The W chromosome is also highly enriched for repeat sequences derived from endogenous retroviruses and likely acts as a "refugium" for these and other retroelements. We annotated 219 putatively functional W-linked genes across at least two evolutionary strata identified based on estimates of sequence divergence between Z and W gametologs. The youngest of these strata is relatively gene-rich, however gene expression across strata suggests retained gene function amidst a greater degree of degeneration following ancient recombination suppression. Functional annotation of W-linked genes indicates a specialization of the W chromosome for reproductive and developmental function since recombination suppression from the Z chromosome.